Eco-Design in the Interior and Its Advantages - M. Kurbanova; M. Adasheva (Genius Journals, 2022)
The article provides a brief description of the eco-style used in modern interiors. The main features and materials of eco-style are described. The principle of selection of plants suitable for interior landscaping, as well as the used phytolamps for organizing additional lighting of plants, is presented.
Keywords: eco-style; eco-design; natural style; interior garden